The Clınıcal Evaluatıon Of “Physıologıc Drıft” (Drıftodontıcs) -A Longıtudınal Study - Enis Güray (Turkish Journal of Orthodontics, 1994)

(untitled)
In the present study of a group of 6 females, 9 males total 15 patients was conducted to evaluate the “Physiologic Drift” or “Driftodontics” of the mandibular teeth following the extraction of four first premolars. Except for the extractions, no other mandibular therapy was rendered. Following a 6.9 months of observation period, the changes on the mandibular structures on the saggital. transverse and horizontal planes were evaluated. Their mean age at the time of extraction was 13.6years. The mesial movement of the molar mesio-buccal cusp and apex was 1.04 mm. and 0.80 mm., respectively and the lower incisors were retroinclinated 5.6°. The canines drifted laterally and distally into the extraction sites while the incisors became more upright over basal bone and less crowded. Incisor irregulanty decreased 3.12 mm.